If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15(t + -6) + 6t = 7(3t + 5) + -11 Reorder the terms: 15(-6 + t) + 6t = 7(3t + 5) + -11 (-6 * 15 + t * 15) + 6t = 7(3t + 5) + -11 (-90 + 15t) + 6t = 7(3t + 5) + -11 Combine like terms: 15t + 6t = 21t -90 + 21t = 7(3t + 5) + -11 Reorder the terms: -90 + 21t = 7(5 + 3t) + -11 -90 + 21t = (5 * 7 + 3t * 7) + -11 -90 + 21t = (35 + 21t) + -11 Reorder the terms: -90 + 21t = 35 + -11 + 21t Combine like terms: 35 + -11 = 24 -90 + 21t = 24 + 21t Add '-21t' to each side of the equation. -90 + 21t + -21t = 24 + 21t + -21t Combine like terms: 21t + -21t = 0 -90 + 0 = 24 + 21t + -21t -90 = 24 + 21t + -21t Combine like terms: 21t + -21t = 0 -90 = 24 + 0 -90 = 24 Solving -90 = 24 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -2(4s-6)-12=-2(6s+5)-2 | | -3(3s-4)-12=-2(8s+10)-2 | | (4x-5)(2x-3)= | | 5x+5=(x-23) | | -18t^4+9t^3+2t= | | .6w-.3w+.2w=3 | | 7y-9y=16 | | 15x-23x=1/3 | | (10b-3)-3(3b+1)=-6 | | f(x)=-7*x^2+5*x+7 | | -2x-10=6x+30-12 | | 2k+6=8k-20+38 | | y=-3/5+3 | | -3/5+3 | | 16=10+32x-16x^2 | | 1454-16x^2=0 | | (x+1)(x+9)-(x-3)(x+5)= | | 1/4x+5/4=9 | | -2.7x^2+35x-3=0 | | 6x+20=8x+4 | | -2.7x^2+35x+3=0 | | 3x+33y=-24 | | 5x+19=8x+7 | | 9+16/4+5*6 | | 19+5-8*4/2 | | 9/10+y/7 | | 9/10+y/1 | | 24/12+5*7 | | -25/8*64/9 | | b/a=15 | | -4(-4v-u)-5(-6u+3v)= | | -31/8*71/9 |